Assessing China's Corporate Sector Vulnerabilities - Chivakul, Mali (IMF Working Papers; Working Paper, 2015)
This paper documents and assesses the risk stemming from rising corporate indebtedness in China using a firm-level dataset of listed firms. It finds that while leverage on average is not high, there is a fat tail of highly leveraged firms accounting for a significant share of total corporate debt, mainly concentrated in the real estate and construction sector and state-owned enterprises in general. The real estate and construction firms tend to face lower borrowing costs and could withstand a modest increase of interest rate shocks despite their high leverage. The corporate sector is however vulnerable to a significant slowdown in the real estate and construction sector. Our sensitivity analysis suggests that the share of debt that would be in financial distress would rise to about a quarter of total listed firm debt in the event of a 20 percent decline in real estate and construction profits.